ANALISIS FAKTOR YANG DAPAT MENUMBUHKAN NIAT PEMBELIAN ULANG SMARTPHONE DI KALANGAN MAHASISWA - Alfianto, Mochamad Rifki; Hartono, Arif; Hartono, Arif (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.11.TAHUN.2022, 2022)
The development of technology today has changed the habits and activities of the people. Along with the development of technology, smartphones are created that help a lot with mobility. Smartphones or smartphones have become an important device and cannot be separated from life. This study aims to examine the effect of perceived price, perceived appearance, perceived value, brand experience, and brand loyalty have a positive effect on repeat purchase intentions. The population in this study were students in Indonesia who had changed smartphones. The sampling technique used is purposive sampling method which produces a sample of 135 respondents. This study uses a quantitative approach. The data used is primary data collected through a questionnaire. The data analysis method used descriptive analysis and structural equation modeling (SEM) analysis which was processed using SmartPLS software. The results of this study indicate that price perception, appearance perception, perceived value, and brand loyalty have a positive and significant effect on repeat purchase intentions. Therefore, related companies can evaluate and develop strategies to attract smartphone repeat purchase intentions.